Preparation method of high-entropy sodium vanadium phosphate electrode
The precursor powder was processed by the rapid Joule thermal method to prepare high-entropy metal-doped vanadium phosphate sodium material, which solved the problems of limited sodium ion transport channels and low conductivity, significantly improved the charge and discharge specific capacity and cycle stability of the material, and provided new ideas for the commercial application of sodium ion batteries.
Patent Information
- Application Number
- CN202411775266.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-05
Smart Images

Figure CN119560491A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a method for preparing a high-entropy sodium vanadium phosphate electrode. Background Art
[0002] As the demand for energy in human production and life continues to rise, the massive consumption of fossil energy such as oil and coal and the pollution to the environment have restricted the development of the energy field. Therefore, future energy storage technology is more inclined to sustainable and low-cost battery technology. In recent years, with the rise of new energy vehicles and energy storage equipment, lithium resources have been over-consumed, so it is extremely important to find a secondary battery that can replace lithium-ion batteries. Sodium and lithium belong to the same main group elements, and their physical and chemical properties are similar. The reserves of sodium resources are more abundant than lithium resources and the cost is lower. Therefore, sodium-ion batteries are gradually coming into our sight and are regarded as one of the most promising substitutes for lithium-ion batteries.
[0003] NASICON-type Na3V2(PO4)3 has the advantages of high voltage platform, high ion diffusion rate and stable crystal structure, and is one of the candidate materials for future commercial sodium-ion batteries. However, the low intrinsic electronic conductivity and low theoretical specific capacity of Na3V2(PO4)3 cathode materials limit their industrial development. At present, the modification methods of NVP mainly focus on its poor conductivity, mainly in the following three aspects: (1) increasing the electronic conductivity of the material through carbon coating; (2) improving the intrinsic conductivity of the material through metal ion doping; (3) improving the electrochemical performance of the material by preparing materials with special morphology. Among them, metal doping can not only improve the conductivity of the electrode, but also activate the high voltage platform to meet the energy density requirements of the cathode material. High entropy metal doping can maximize the kinetic transport capacity of the electrode to a certain extent. However, the current traditional preparation methods are not enough to fully exert the advantages of high entropy metal-doped sodium vanadium phosphate, especially for the sodium storage capacity in the low voltage platform area.
[0004] In view of the problems existing in the current high entropy metal-doped sodium vanadium phosphate, a rapid Joule heat preparation method is used to stabilize the cathode structure and increase the sodium storage sites, thereby improving the electrochemical performance of the material. High entropy sodium vanadium phosphate prepared by Joule heat not only has excellent sodium ion diffusion capacity, but also can accommodate additional sodium ions, thereby increasing the capacity of the electrode; in addition, this rapidly prepared cathode has excellent structural stability, thereby achieving excellent cycle stability. Summary of the invention
[0005] The purpose of the present invention is to solve the limiting factors of limited sodium ion transport channels, low intrinsic electronic conductivity, poor stability and other limitations of high entropy metal-doped sodium vanadium phosphate positive electrode materials, and to develop new high entropy sodium vanadium phosphate material synthesis and modification strategies. The powder precursor is treated by rapid Joule heating to prepare a high entropy metal-doped sodium vanadium phosphate material. The expansion of sodium ion transport channels and the improvement of conductivity are achieved simultaneously, thereby improving the charge and discharge specific capacity and cycle stability of the high entropy sodium vanadium phosphate positive electrode material.
[0006] The present invention is implemented by the following technical scheme: A method for preparing a high entropy sodium vanadium phosphate electrode comprises the following steps:
[0007] Step 1, add 2.7g ammonium vanadate and 16.8g oxalic acid into 200mL deionized water, stir and react at 60-120°C for 20-80min;
[0008] Step 2, after cooling slightly, add 0.75g of ferric nitrate, 0.81g of manganese nitrate, 0.80g of chromium nitrate, 0.58g of cobalt nitrate and 0.49g of nickel nitrate dissolved in 100mL of deionized water;
[0009] Step 3, after stirring, add 8.3 g of sodium dihydrogen phosphate dissolved in 100 mL of deionized water, and then evaporate the solution by magnetic stirring and grind to obtain a precursor powder;
[0010] Step 4, subjecting the precursor powder to rapid Joule heating to obtain an improved high entropy metal-doped sodium vanadium phosphate sodium ion battery positive electrode material powder;
[0011] Step 5: prepare a slurry according to the ratio of the prepared high entropy metal-doped sodium vanadium phosphate powder: conductive carbon black: binder = 70:20:10, grind it thoroughly in an agate mortar and apply it, dry it and cut it into discs with a diameter of 14 mm to obtain the high entropy sodium vanadium phosphate electrode sheet.
[0012] Preferably, the high-valent vanadium source may be any one of sodium vanadate, sodium metavanadate, ammonium metavanadate, and vanadium pentoxide, or a combination of at least two of them.
[0013] Preferably, the phosphorus source can be any one of phosphoric acid, sodium phosphate, sodium metaphosphate or sodium dihydrogen phosphate, or a combination of at least two thereof. Typical but non-limiting examples of the combination include: a combination of phosphoric acid and sodium phosphate, and a combination of sodium phosphate and sodium dihydrogen phosphate.
[0014] Preferably, in step 3, the suspension is obtained by stirring on a magnetic stirrer for 8-12 hours; and the molar ratio of ammonium vanadate, oxalic acid, sodium dihydrogen phosphate, ferric nitrate, manganese nitrate, chromium nitrate, cobalt nitrate and nickel nitrate is 0.75:4:3:0.1:0.1:0.1:0.1:0.1.
[0015] Preferably, the rapid Joule heating is set to have a current of 50A-70A and a time of 10-120s.
[0016] Preferably, in step 5, the electrode coating thickness is 10-30 um.
[0017] A sodium ion battery is assembled with a high entropy sodium vanadium phosphate electrode sheet as a positive electrode, a metal sodium sheet as a negative electrode, and a glass fiber as a separator. The specification is GF / D, and a 1 mol / L sodium perchlorate solution is used as an electrolyte.
[0018] The preparation method of high entropy sodium vanadium phosphate battery includes the following steps: in a glove box filled with argon atmosphere, a positive electrode shell, a positive electrode sheet, a diaphragm are placed in sequence, and then an appropriate amount of electrolyte, a sodium sheet, a stainless steel gasket, a spring, and a negative electrode shell are added. Then, a packaging machine is started to compress and package the battery.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The present invention adopts a chemical synthesis method to prepare a precursor, and adopts a Joule heating process to prepare a high entropy metal-doped sodium vanadium phosphate positive electrode material. Compared with traditional calcination, the rapid Joule heating of this process reaction not only has a fast heating speed, but also has low energy consumption. The reaction conditions are mild, the product has high purity, good particle size uniformity, and it is easy to control the proportion of each component, and it can be prepared continuously.
[0021] 2. The high-entropy metal-doped sodium vanadium phosphate positive electrode material prepared by the present invention simultaneously realizes the expansion of sodium ion transport channels and the improvement of conductivity, thereby improving the charge and discharge specific capacity and cycle stability of the high-entropy metal-doped sodium vanadium phosphate positive electrode material, and provides new ideas and solutions for the further commercial application of sodium ion batteries in the future. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the X-ray diffraction (XRD) pattern of the high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention.
[0023] Figure 2 It is a comparison diagram of cyclic voltammetry (CV) curves of sodium ion batteries prepared with the high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention at a scan rate of 0.1mVs-1.
[0024] Figure 3 It is a charge and discharge curve diagram of a sodium ion battery using a high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention at a rate of 0.2C.
[0025] Figure 4 It is a cycle performance diagram of a sodium ion battery using a high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention at a 1C rate.
[0026] Figure 5 It is a cycle performance diagram of a sodium ion battery using a high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention at a 5C rate.
[0027] Figure 6 It is a rate performance diagram of a sodium ion battery using a high entropy sodium vanadium phosphate-Joule heat positive electrode material prepared by the present invention at 0.5-10C. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that, under the premise of no conflict, the various embodiments or technical features described below can be arbitrarily combined to form a new embodiment.
[0029] The chemical reagents used in the present invention are all analytically pure ammonium vanadate, sodium dihydrogen phosphate, oxalic acid, ferric nitrate, manganese nitrate, chromium nitrate, cobalt nitrate and nickel nitrate, and the purity of the inert gas (argon) used in step 1 is 99.999%. The aluminum foil and diaphragm used in step 2 were purchased from Suzhou Duoduo Chemical Technology Co., Ltd.
[0030] Example 1: A method for preparing a high entropy sodium vanadium phosphate electrode, comprising the following steps:
[0031] Add 2.7g of ammonium vanadate and 16.8g of oxalic acid to 200mL of deionized water, stir and react for 20-80min at 60-120℃, and add 0.75g of ferric nitrate, 0.81g of manganese nitrate, 0.80g of chromium nitrate, 0.58g of cobalt nitrate and 0.49g of nickel nitrate dissolved in 100mL of deionized water after cooling slightly. After stirring, add 8.3g of sodium dihydrogen phosphate dissolved in 100mL of deionized water, and then stir and evaporate the solution and grind it to obtain a precursor powder. The precursor powder is subjected to rapid Joule heating, and the improved high entropy metal-doped sodium vanadium phosphate sodium ion battery positive electrode material powder is obtained. After the sample is taken out, it is fully ground and washed and centrifuged to remove the influence of impurities. When washing the sample, first place the sample powder in a centrifuge tube, add an appropriate amount of ethanol, and set the speed to 12000r min after ultrasound. -1 , time 5min, then dried and collected.
[0032] The positive electrode active material, conductive black, and polyvinylidene fluoride (PVDF) were added to a mortar at a mass ratio of 7:2:1 and ground for 20 minutes to make them uniform. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added and ground into a uniform slurry, which was then coated on the surface of aluminum foil and dried to obtain a working electrode. A circular electrode sheet with a diameter of 12 mm was formed by a punching machine, and the active material loading of the electrode sheet was 1.5-1.7 mg cm-2.
[0033] Example 2: Assembly of sodium ion batteries: Assemble sodium ion batteries in a glove box filled with argon atmosphere, wherein the water content is less than 0.01ppm and the oxygen content is less than 0.01ppm. During assembly, place the positive electrode sheet prepared in step 2 in the positive battery shell, place a glass fiber diaphragm, add a 1M NaClO4 solution electrolyte, then place the sodium sheet, stainless steel gasket, shrapnel, and negative electrode shell in sequence, and finally seal the glove box with an air pressure packaging machine. The prepared positive electrode material powder is subjected to phase and purity characterization tests, such as phase analysis by X-ray diffraction method and high-resolution transmission electron microscopy to determine the structure and distribution of each component in the test object. The prepared battery is activated and then subjected to electrochemical performance testing. During activation, the charge and discharge current for the first three cycles is 0.2C, and then the test is performed at 1C, where the theoretical specific capacity at a 1C rate is 176mAh g -1 The test voltage range is 1.2~4.2V. The cyclic voltammetry curve of the material at a scanning speed of 0.1mV / s is shown in Figure 2 As shown, the initial charge and discharge curve of the material at 0.2C current is as follows Figure 3 The cycling performance at 1C and 5C rates is shown in Figure 4 and Figure 5 As shown, the rate performance at 0.5C to 10C is as follows Figure 6 shown.
[0034] Result analysis:
[0035] As attached Figure 1 As shown, the prepared cathode material was analyzed by X-ray diffraction method, and the obtained diffraction peaks corresponded to the standard card of sodium vanadium phosphate (JCPDS NO.53-0018). This shows that the synthesized new cathode material does not affect the integrity of the crystal structure, and all of them are hexagonal NASICON structures without impurities.
[0036] As attached Figure 2 As shown, the cyclic voltammetry (CV) curves of the high entropy sodium vanadium phosphate-Joule heat sodium ion battery prepared by the present invention and the high entropy sodium vanadium phosphate-traditional calcined sodium ion battery at a scan rate of 0.1mV / s are compared. It can be seen that compared with the traditional calcined material, the redox peak of the high entropy sodium vanadium phosphate-Joule heat at around 1.6V is significantly enhanced, indicating that the amount of sodium ions deintercalated in the process is increased, which is beneficial to improve the charge and discharge capacity of the material.
[0037] As attached Figure 3 As shown in the figure, the first charge and discharge curve at 0.2C. It can be seen from the figure that the material exhibits a typical charge and discharge platform curve unique to sodium ion batteries. The initial discharge capacity of the sodium ion battery after rapid Joule heating can reach 174.6mAh g -1The initial discharge capacity of the sodium-ion battery prepared by high-entropy sodium vanadium phosphate-conventional calcined cathode material is only 148.5 mAh g -1 .
[0038] As attached Figure 4 As shown in the figure, the cycle performance test was carried out at a 1C rate. After 100 cycles of high entropy sodium vanadium phosphate-Joule heat, the reversible discharge capacity increased from 149.4 mAh g -1 Down to 146.2mAh g -1 The capacity retention rate is 97.86%, which reflects the good long-cycle stability at low current density.
[0039] As attached Figure 5 As shown in the figure, the cycle performance test was carried out at a 5C rate. After 700 cycles of high entropy sodium vanadium phosphate-Joule heat, the reversible discharge capacity increased from 137.5 mAh g -1 Down to 125.0mAh g -1 The capacity retention rate is 90.91%, which reflects the good long-cycle stability under high current density.
[0040] As attached Figure 6 As shown, the discharge specific capacities of the embodiments at 0.5C, 1C, 2C, 3C, 4C, 5C, 6C, 7C, 8C, 9C and 10C rates are 155.39 mAh g -1 , 148.49mAh g -1 , 144.23mAh g -1 , 141.22mAh g -1 , 138.83mAh g -1 、136.55mAhg -1 、134.47mAhg -1 , 132.52mAh g -1 , 130.65mAh g -1 , 128.51mAh g -1 and 126.61mAhgg -1 When the current returned to 1C, the capacity returned to 148.06 mAh g -1 The capacity retention rate is 95.27%, which fully proves the excellent rate performance of the modified sodium-ion battery.
[0041] Therefore, it can be seen from the experimental data that the positive electrode material of high entropy metal doped sodium vanadium phosphate using Joule heat shows good electrochemical performance in terms of charge and discharge specific capacity, cycle performance and rate performance in sodium ion batteries, and has great development prospects.
[0042] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing a high entropy sodium vanadium phosphate electrode, characterized in that: The steps include: Step 1, add 2.7g ammonium vanadate and 16.8g oxalic acid into 200mL deionized water, stir and react at 60-120°C for 20-80min; Step 2, after cooling slightly, add 0.75g of ferric nitrate, 0.81g of manganese nitrate, 0.80g of chromium nitrate, 0.58g of cobalt nitrate and 0.49g of nickel nitrate dissolved in 100mL of deionized water; Step 3, after stirring, add 8.3 g of sodium dihydrogen phosphate dissolved in 100 mL of deionized water, and then evaporate the solution by magnetic stirring and grind to obtain a precursor powder; Step 4, subjecting the precursor powder to rapid Joule heating to obtain an improved high entropy metal-doped sodium vanadium phosphate sodium ion battery positive electrode material powder; Step 5: prepare a slurry according to the ratio of the prepared high entropy metal-doped sodium vanadium phosphate powder: conductive carbon black: binder = 70:20:10, grind it thoroughly in an agate mortar and apply it, dry it and cut it into discs with a diameter of 14 mm to obtain the high entropy sodium vanadium phosphate electrode sheet.
2. The method for preparing a high entropy sodium vanadium phosphate electrode according to claim 1, characterized in that: The high-valent vanadium source may also be any one of sodium vanadate, sodium metavanadate, ammonium metavanadate, and vanadium pentoxide, or a combination of at least two of them.
3. The method for preparing a high entropy sodium vanadium phosphate electrode according to claim 1, characterized in that: The phosphorus source can be any one of phosphoric acid, sodium phosphate, sodium metaphosphate or sodium dihydrogen phosphate, or a combination of at least two of them. Typical but non-limiting examples of the combination include: a combination of phosphoric acid and sodium phosphate, and a combination of sodium phosphate and sodium dihydrogen phosphate.
4. The method for preparing a high entropy sodium vanadium phosphate electrode according to claim 1, characterized in that: In the step 3, stirring is carried out on a magnetic stirrer for 8-12 hours to obtain a suspension; and the molar ratio of ammonium vanadate, oxalic acid, sodium dihydrogen phosphate, ferric nitrate, manganese nitrate, chromium nitrate, cobalt nitrate and nickel nitrate is 0.75:4:3:0.1:0.1:0.1:0.1:0.
1.
5. The method for preparing a high entropy sodium vanadium phosphate electrode according to claim 1, characterized in that: The rapid Joule heating is set to have a current of 50A-70A and a time of 10-120s.
6. The method for preparing a high entropy sodium vanadium phosphate electrode according to claim 1, characterized in that: In step 5, the electrode coating thickness is 10-30 um.
7. A sodium ion battery, with a high entropy sodium vanadium phosphate electrode sheet as the positive electrode, a metal sodium sheet as the negative electrode, a glass fiber as the separator, a specification of GF / D, and a 1 mol / L sodium perchlorate solution as the electrolyte to assemble the battery.
8. The method for preparing a battery according to claim 7, characterized in that: In a glove box filled with argon atmosphere, put the positive electrode shell, positive electrode sheet, and diaphragm in order, and then add appropriate amount of electrolyte, sodium sheet, stainless steel gasket, spring, and negative electrode shell. Then use the start packaging machine to press and package the battery.
Citation Information
Patent Citations
Method for synthesizing sodium vanadium phosphate / carbon positive electrode composite material by rapid high-temperature thermal shock method
CN115650199A
Sodium vanadium fluorophosphate material synthesized by instantaneous Joule thermal sintering and preparation method and application thereof
CN115744866A
Doped polyion material, preparation method and application
CN116632230A
Quentabasic metal co-doped high-entropy sodium vanadium phosphate positive electrode material as well as preparation method and application thereof
CN118522886A
Preparation method of modified sodium vanadium phosphate positive electrode material
CN118833793A
Cited By
Sodium vanadium phosphate composite positive electrode material and preparation method and application thereof
CN120463171A